Hello, bookstore [videorecording (DVD)] - Tannenbaum, Matt (Kino Lorber, Inc., 2022)
In the shadow of the pandemic, a small town rallies to protect a beloved local bookstore. A landmark in Lenox, Massachusetts, The Bookstore is a magical, beatnik gem thanks to its owner Matt Tannenbaum, whose passion for stories runs deep.